Neurotracker Training to Improve The Archery Athlete Concentration - Komarudin, K; Sagitarius, S; Sartono, Hadi; Awaludin, Patriana Nurmansyah; Hidayatullah, Gilang Ginanjar (Universitas Pendidikan Indonesia, 2020)
Neurotracker is a 3D technology with Multiple Object Tracking (MOT). This technology has not been developed in Indonesia. Meanwhile, developed countries have implemented this technology in sport training, including in archery sport. In archery sport, the athletes are required to concentrate every time they perform a technique and to be fast and accurate in making a decision when aiming and releasing the arrows. The problem usually occurs during shooting is that the athlete doubts in aiming and releasing the arrows, thus the shooting result does not hit the target. It is caused by the athlete’s doubt and the lack of concentration. To overcome the problem, a neurotracker training is important to be conducted in every training process to improve the athletes’ concentration. The method used in this study was an experimental method. The samples were 20 persons chosen in a non-random sampling. The subjects were divided into two groups through a random assignment, thus the number of subject in each group was ten persons. The instrument to measure the concentration was the Concentration Grid Test. The design of the study was pretest-posttest control group design. To analyze the data, t-test was used. The result of the study showed that (1) there was a significant effect of the NeuroTracker training on the improvement of the archery athlete’s concentration, (2) there was a significant effect of conventional training on the improvement of archery athlete’s concentration, (3) there was a significant difference of effect between the NeuroTracker training and conventional training in the improvement of the archery athlete’s concentration. The NeuroTracker training was better than a conventional training in increasing the archery athlete’s concentration. It is suggested that the archery trainers implement the NeuroTracker technology in the training process as it could improve the concentration of the archery athletes.